2021
DOI: 10.1002/acn3.51333
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of unilateral and bilateral pallidotomy for primary dystonia

Abstract: Objective Ablation of the globus pallidus internus (pallidotomy) is an effective surgical intervention for dystonia. However, the current literature on the efficacy and safety of pallidotomy for dystonia is derived only from single‐case reports and small cohort studies. Methods We retrospectively analyzed patients with primary dystonia who underwent pallidotomy at our institution between 2014 and 2019. Neurological conditions were evaluated using the Burke‐Fahn‐Marsden Dystonia Rating Scale (BFMDRS, range: 0–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 42 publications
1
31
1
Order By: Relevance
“…We have previously reported that unilateral pallidotomy significantly improved cervical dystonia with a 47.9% reduction in TWSTRS total score at the 6‐month postoperative evaluation 37 . Additionally, a recent study has shown that bilateral and unilateral pallidotomies improved cervical dystonia with 73% and 50% reduction on the neck subscale of BFMDRS, respectively 27 . The STN is also an available target of DBS for cervical dystonia in a limited number of studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported that unilateral pallidotomy significantly improved cervical dystonia with a 47.9% reduction in TWSTRS total score at the 6‐month postoperative evaluation 37 . Additionally, a recent study has shown that bilateral and unilateral pallidotomies improved cervical dystonia with 73% and 50% reduction on the neck subscale of BFMDRS, respectively 27 . The STN is also an available target of DBS for cervical dystonia in a limited number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possible adverse effects of pallidotomy or pallidothalamic tractotomy are different because of the surrounding structures. In 69 patients with dystonia who underwent unilateral pallidotomy, delayed cerebral infarction at the PLIC in three patients (4.4%), hemiparesis in two patients (2.9%), and visual disturbance in one patient (1.4%) were reported 27 . These complications were strongly associated with injury to adjacent structures of the GPi, including the PLIC (medial to GPi) leading to hemiparesis and optic tract (caudal to GPi) leading to visual field disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have performed several neurosurgical treatments for dystonia, including selective peripheral denervation, deep brain stimulation (DBS), and ablative surgeries using radiofrequency, gamma knife, and focused ultrasound ( 14 19 ). All surgical candidates in those reports were refractory to conventional oral medications including trihexyphenidyl, clonazepam, and baclofen.…”
Section: Introductionmentioning
confidence: 99%